2017
DOI: 10.1016/j.juro.2017.04.067
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with Renal Cell Carcinoma and Sarcomatoid Dedifferentiation Treated with Nephrectomy and Systemic Therapies: Comparison between the Cytokine and Targeted Therapy Eras

Abstract: Purpose To study the overall survival and prognostic factors of patients with sarcomatoid renal cell carcinoma treated with nephrectomy and systemic therapy in the cytokine and targeted therapy eras. Materials and Methods This is a retrospective study of patients with sarcomatoid renal cell carcinoma who had nephrectomy and received systemic therapy at our center in the cytokine era (1987–2005) or the targeted therapy era (2006–2015). Multivariate regression models were used to determine the association of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 30 publications
(24 reference statements)
4
50
0
Order By: Relevance
“…Compared to the cytokine therapy era, the targeted therapy era has achieved significant improvement in survival in RCC. However, RCC with sarcomatoid differentiation has been shown to have a poor response to targeted therapy [4,29], and this may influence prognosis and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the cytokine therapy era, the targeted therapy era has achieved significant improvement in survival in RCC. However, RCC with sarcomatoid differentiation has been shown to have a poor response to targeted therapy [4,29], and this may influence prognosis and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery alone is often an inadequate measure to cure patients (10)(11)(12). Furthermore, SRCC does not respond well to cytotoxic chemotherapy, cytokines and targeted therapies (9,13). A higher percentage of sarcomatoid features are also associated with a poorer survival (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…reported 167 succumbed with median OS being 16.5 months (94% at six months, 67% at 12 months, 38% at two years, 14% at five years). 3 Chemotherapy did not improve OS in their cohort however, there was a trend towards improved survival in the era of targeted therapy. Recently, a phase III randomized, double-blind, placebo controlled trial with adjuvant sunitinib was reported by Ravaud and colleagues.…”
Section: Discussionmentioning
confidence: 87%
“…The overall survival (OS) for patients with sRCC can be as little as 4 months. 3 We present a case of sRCC that recurred rapidly in the nephrectomy bed despite negative margins in the pathology specimen.…”
Section: Introductionmentioning
confidence: 97%